The Role of Islamic Education in Building Students' Character at SMP Negeri 17 Surabaya - Mas ruroh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Keywords: Islamic Education, Character Building, Role. It is an opportunities for educator to give contribution in effort to form character, hence expected formation of student character can be pursued through Islamic education taught in school. The formulation of the problem in this research, first, how is the learning process of Islamic education at SMP Negeri 17 Surabaya? second, how is the character of students at SMP Negeri 17 Surabaya? third, how is the role of Islamic education in building students’ character at SMP Negeri 17 Surabaya?Qualitative approach is used as the methodology in this research. Data are collected through observation, documentation and interview. The data are analyzed using descriptive analysis technique. Researcher describeds the creativity of the teachers of Islamic education in this school.The results of the study could be summarized as follows: first, in order to to keep the implementation of Islamic education run in accordance with the objectives: a) Prepare the instructional design as early as possible including: educational calendar, learning units and fun lessons; b) follow curriculum for Islamic education designed by Ministry of National Education; c) Use the following teaching method in learning process: lecturing, question-answer, demonstration and assignment; d) Conduct pretest and post test evaluation including formative and summative evaluations. Second, many variables show that students have had a good character although not all elements of their personality is good. Islamic Education has significant role in building the character of students for the provision of life in the earth and the hereafter in accordance with the guidance of Al-Qur'an and Hadith. This is all also because of the encouragement of the principal and other teachers. Basically every human wants to have a sympathetic personality, because, with it, humans will be respected, and loved by people around.